Bacteria Remediate the Effects of Food Additives on Intestinal Function in an in vitro Model of the Gastrointestinal Tract - Malik, Mridu; Subedi, Sanjeena; Marques, Cláudia N. H.; Mahler, Gretchen J. (Frontiers in Nutrition, 2020)
As the site of nutrient absorption, the small intestine is continuously exposed to preservatives and additives present in consumed food. While the effects of diet on the lower gastrointestinal tract is widely studied, the effects of food additives on the small intestinal epithelium and microbiota are less clearly understood. The goal of this work was to develop and establish a physiologically relevant model of the upper gastrointestinal tract to study the complex interactions between food additives, individual bacterial species, and intestinal function. To achieve this, an in vitro model incorporating simulated digestion, human intestinal epithelial cells, and the commensal, Gram-positive Lactobacillus rhamnosus, or the opportunistic, Gram-negative Escherichia coli was developed. This model was used to assess intestinal permeability and alkaline phosphatase activity following exposure to high glucose (HG), salt, emulsifier (TWEEN 20), food (milk chocolate candies) or chemical-grade titanium dioxide nanoparticles (TiO2-NP), and food (whole wheat bread) or chemical-grade gluten. It was found that HG increased intestinal permeability, the presence of bacteria remediated the negative effects of HG on intestinal permeability, and a decrease in permeability and IAP activity was observed with increasing concentration of TWEEN 20 both in the presence and absence of bacteria. While L. rhamnosus influenced the activity of intestinal alkaline phosphatase and tight junction protein distribution, E. coli produced indole to reinstate intestinal permeability. The source of TiO2 and gluten led to altered impacts on permeability and IAP activity. The growth of E. coli and L. rhamnosus was found to depend on the type of food additive used. Overall, the presence of bacteria in the in vitro model influenced the effects of food additives on intestinal function, suggesting a complex association between diet and upper GI microbiota. This model provides a method to study small intestinal function and host-microbe interactions in vitro in both healthy and diseased conditions.